2018
DOI: 10.1002/bies.201700237
|View full text |Cite
|
Sign up to set email alerts
|

Understanding Animal Evolution: The Added Value of Sponge Transcriptomics and Genomics

Abstract: Sponges are important but often-neglected organisms. The absence of classical animal traits (nerves, digestive tract, and muscles) makes sponges challenging for non-specialists to work with and has delayed getting high quality genomic data compared to other invertebrates. Yet analyses of sponge genomes and transcriptomes currently available have radically changed our understanding of animal evolution. Sponges are of prime evolutionary importance as one of the best candidates to form the sister group of all oth… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
26
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(27 citation statements)
references
References 120 publications
(195 reference statements)
1
26
0
Order By: Relevance
“…An initially surprising finding from early genome and transcriptome sequencing of sponges was that, despite having vast morphological differences with other animals, they also have highly conserved homologs of most developmental regulatory genes (Nichols, Dirks, Pearse, & King, ; Renard et al, ; Srivastava et al, ). Furthermore, it has been shown that these genes have spatiotemporal expression patterns consistent with conserved roles in developmental patterning.…”
Section: Plasticity May Predominate Over Genetic Patterning In Spongementioning
confidence: 99%
“…An initially surprising finding from early genome and transcriptome sequencing of sponges was that, despite having vast morphological differences with other animals, they also have highly conserved homologs of most developmental regulatory genes (Nichols, Dirks, Pearse, & King, ; Renard et al, ; Srivastava et al, ). Furthermore, it has been shown that these genes have spatiotemporal expression patterns consistent with conserved roles in developmental patterning.…”
Section: Plasticity May Predominate Over Genetic Patterning In Spongementioning
confidence: 99%
“…With regard to the evolution of poriferan-TSP, our analysis demonstrated that all three categories of TSP-related proteins are expressed in this phylum. As others have noted more generally, there was very high in-clade sequence variation between different classes of Porifera (Renard et al. 2018).…”
Section: Discussionmentioning
confidence: 65%
“…Their body differs from those of all other metazoan, because instead of having true muscles and neurons, the sponges basically have a choanoderm (internal flagellated epithelium; [the term epithelium is used in this work in accordance to the definition proposed by Nickel, Scheer, Hammel, Herzen, and Beckmann () that sponges have epithelium sensu lato ]), a pinacoderm (coating epithelium) lining the wall of the canals of the aquiferous system, and a mesohyl between these two layers, which comprises mobile cells, skeletal material (spicules), and protein fibers (Langenbruch, ; Leys & Hill, ). Nonetheless, although morphologically simple, the genome, transcriptome, life cycle, and other aspects of their biology were characterized as more complex than expected (Dunn, Leys, & Haddock, ; Leys & Hill, ; Renard, Leys, Wörheide, & Borchiellini, ). The filter‐feeding habit of sponges is crucial for the health and economy of marine environments, by transferring nutrients from the water column to the benthic communities (benthic‐pelagic coupling), interfering in the carbon and silicon cycles, and due to their constant cell changes, providing particulate organic carbon that will serve as food for microorganisms present in water and boost the trophic nets (Becerro, ; de Goeij et al, ).…”
Section: Introductionmentioning
confidence: 98%